Ein Superstar der neueren finnischen Prosa. Einige Bemerkungen zum finnischen Roman "Fegefeuer" von Sofi Oksanen - Mrozewicz, Bolesław (Folia Scandinavica Posnaniensia, 2016)
The article is devoted to Sofi Oksanen, one of the most recognizable Finnish authors of the young generation whose literary production has been an unbroken streak of success for the last ten years. It addresses in particular her groundbreaking novel Purge (Puhdistus). In the analysis, the article focuses first and foremost on the aspect of a woman’s corporeality as well as shame and exclusion resulting from sexual abuse. It is one of the central motifs in Osanen’s production. On the example of Aliide the writer depicts, from the feminist point of view, the effects of physical violence towards women used as an element of humiliation and oppression of a conquered nation. The metaphor of a woman’s body as an occupied country gives the novel a universal character and draws attention to the fact that destroying womanhood is a subtle and slow way to the fall of societies. Therefore the deeds of both women are not unambiguously condemned in the novel.